E-140 Focal cooling through a novel insulated catheter allows fast and safe therapeutic hypothermia in a canine ischemic stroke model. (22nd July 2018) - King, R; Mitchell, J; Brooks, O; Licwinko, J; Abou-Chebl, A; Merrill, T; Gounis, M; Caroff, J
Abstract : Introduction: Mechanical thrombectomy has dramatically improved the prognosis of acute ischemic stroke. Despite high recanalization rates, nearly 50% of eligible patients will still not present a good outcome. 1 Neuroprotective effects of therapeutic hypothermia (TH) have been demonstrated in multiple animal studies but the side effects of whole body cooling might impair the potential clinical benefits of TH. 2 The purpose of this study was to investigate whether at-risk brain tissue could be rapidly and deeply cooled using a novel carotid catheter in an ischemia/reperfusion canine model. This innovative insulated local cooling catheter would potentially deliver temperatures significantly colder than with standard devices while requiring less fluid and time to achieve target temperatures and thereby minimizing the risks of systemic adverse events. Materials and methods: A temporary MCA occlusion using an embolic coil was created in a canine. 3 Concurrent with MCA occlusion, cold isotonic saline was delivered directly into the ipsilateral ICA. In Phase I (n=4), brain tissue temperatures were measured using intra-cerebral probes (figure 1). Saline flow rate was varied to meet a target MCA infarct region temperature of 30°C. 4 In Phase II (n=7), animals underwent TH at the determined flow rate. Cooling was initiated 5 min before removing the embolic coil and continued for an additional 20 min of reperfusion following 45 min of total occlusion duration. Hemodynamic parameters and arterial blood gases were continuously evaluated. The resulting infarct size was measured using MR-ADC imaging. Results: In Phase I, target tissue cooling rates were 2.2±2.5°C/min at 20–40 ml/min with an observed minimum temperature of 23.8°C, without evidence of systemic cooling. To best achieve target temperature without overshoot, a flow rate of 22 ml/min was selected. In Phase II, local cooling was well tolerated with minimal impact on core temperature (38.0°C±0.6°C baseline; 37.2°C±0.5°C post cooling) and hematocrit (35%±7% baseline; 30%±7% post cooling). Infarct size was obtained for 3 animals and measured 0.2±0.2 cm 3, which tended to be smaller than the mean stroke volume of 3.5±3.4 cm 3 (p=0.09) found in historical control animals (n=6) with an occlusion time of 44±7.9 min. Conclusions: This work demonstrated that focal brain TH can be quickly and safely achieved through a novel insulated carotid catheter. The subsequent small infarct volumes suggest potential benefit for this approach. References: Lancet 2016. JoCBF&M 2014. Brain Res Bull 2016. Brain 2007. Disclosures: R. King: None. J. Mitchell: 1; C; NIH grant #5R43NS095573–02. 5; C; Employee of FocalCool LLC. O. Brooks: None. J. Licwinko: 1; C; NIH grant #5R43NS095573–02. 5; C; FocalCool LLC. A. Abou-Chebl: 1; C; NIH grant #5R43NS095573–02. T. Merrill: 1; C; NIH grant #5R43NS095573–02. 5; C; Employee of FocalCool LLC. M. Gounis: None. J. Caroff: None.